The sustainable development of tourism industry in Fujian Province under the impact of the Covid-19 - Chen, Bolun; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
Under the normalization of the prevention of the new crown epidemic, the cultural tourism industry has been severely impacted, causing the entire tourism industry to press the pause button and unable to develop normally. The vision is to better adjust the existing problems, collect and summarize information from various places through the second-hand data collection method, make comparisons, and then combine the local characteristics of Fujian Province with the situation to help the sustainable development of the local tourism industry in Fujian Province.